2021
DOI: 10.3390/buildings11120567
|View full text |Cite
|
Sign up to set email alerts
|

Megaproject Management Research: The Status Quo and Future Directions

Abstract: Megaproject practices worldwide have triggered increasing research in megaproject management issues and led to an increasing number of papers being published during the last decade. However, it is demonstrated by the literature that there is no systematic examination on research development in the discipline of megaproject management, and consequently it is very difficult for scholars to quickly understand and grasp the research trend. Therefore, a research question naturally comes out, i.e., what is the statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…A complexidade do tema mostra que há ainda muito a ser explorado acerca dos diversos aspectos de gerenciamento de projetos. A análise realizada, baseada em bibliometria, aponta os subtemas de gestão de riscos, stakeholders, sustentabilidade ambiental e governança como as principais áreas nas quais pesquisas estão sendo realizadas, o que corrobora direções de pesquisa apontadas em outras revisões publicadas recentemente (YUAN et al, 2021). Isso pode ser explicado pela maturidade da pesquisa na área, juntamente ao crescimento da preocupação com a governança em projetos de forma geral.…”
Section: Conclusãounclassified
“…A complexidade do tema mostra que há ainda muito a ser explorado acerca dos diversos aspectos de gerenciamento de projetos. A análise realizada, baseada em bibliometria, aponta os subtemas de gestão de riscos, stakeholders, sustentabilidade ambiental e governança como as principais áreas nas quais pesquisas estão sendo realizadas, o que corrobora direções de pesquisa apontadas em outras revisões publicadas recentemente (YUAN et al, 2021). Isso pode ser explicado pela maturidade da pesquisa na área, juntamente ao crescimento da preocupação com a governança em projetos de forma geral.…”
Section: Conclusãounclassified
“…Several previous studies have shown that the management of megaprojects is based on four aspects: contract management, cost management, stakeholder management and value management (Ramani and Lingan, 2022; Yuan et al , 2021), and the successful completion of this type of project is conditioned by the best quality management (Chang, 2013; Invernizzi et al , 2019; Zeng et al , 2014). Therefore, poor management of desired value and non-conformities is a reliable indicator of construction project failure.…”
Section: Introductionmentioning
confidence: 99%
“…Megaprojects have been significant drivers and boosters of economic and social development [1]. Thus, both public and private organisations and governments worldwide have resorted to the development of megaprojects as one of the most preferential routes to provide benefits to local municipalities and society [2].…”
Section: Introductionmentioning
confidence: 99%